2016
DOI: 10.1007/s12264-016-0036-7
|View full text |Cite
|
Sign up to set email alerts
|

Sleep and Cognitive Abnormalities in Acute Minor Thalamic Infarction

Abstract: In order to characterize sleep and the cognitive patterns in patients with acute minor thalamic infarction (AMTI), we enrolled 27 patients with AMTI and 12 matched healthy individuals. Questionnaires about sleep and cognition as well as polysomnography (PSG) were performed on days 14 and 90 post-stroke. Compared to healthy controls, in patients with AMTI, hyposomnia was more prevalent; sleep architecture was disrupted as indicated by decreased sleep efficiency, increased sleep latency, and decreased non-rapid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…Neuropsychological examination and brain imaging studies have indicated that narcolepsy influences executive function and emotional and cognitive processing [3943]. Executive function requires the control and coordination of several cognitive domains including working memory and reward sensitivity [44, 45]. Both working memory and reward sensitivity are functionally coordinated by prefrontal and mesial-frontal regions [1], which are abundantly linked to the hypocretin system [2, 46].…”
Section: Discussionmentioning
confidence: 99%
“…Neuropsychological examination and brain imaging studies have indicated that narcolepsy influences executive function and emotional and cognitive processing [3943]. Executive function requires the control and coordination of several cognitive domains including working memory and reward sensitivity [44, 45]. Both working memory and reward sensitivity are functionally coordinated by prefrontal and mesial-frontal regions [1], which are abundantly linked to the hypocretin system [2, 46].…”
Section: Discussionmentioning
confidence: 99%
“…The thalamo-frontal circuit [16][17][18] as well as the cortico-thalamo-basal ganglia-cortical circuit [8,16] are crucial in the recovery from DOCs, and atrophy of the thalamus has been found to be proportional to the severity of DOCs [8]. In addition to its function in DOCs, some studies have also shown that the thalamus is important in many aspects of forebrain function through various projection patterns, such as those that control alertness, attention, and awareness, and those that regulate sleep-wake rhythms [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…8 An increase in sleep duration or need is particularly often found in patients with (bilateral) lesions of the paramedian thalamus. 6,9 Symptoms such as fatigue, insomnia, and EDS are common after stroke. 10,11 Restless legs syndrome (RLS), in contrast, does not seem to be more prevalent after stroke than in the general population.…”
Section: Subjective Assessmentsmentioning
confidence: 99%